Comparison of effectiveness and efficiency of electron beam over gamma rays to induce novel mutations in mungbean (Vigna radiata L. Wilczek). (April 2023) - Dhole, Vinod Janardan; Souframanien, J.; Reddy, Kandali Sreenivasulu; Petwal, Vikash Chandra
Abstract: Induced mutation is very useful in mungbean as it is having less natural genetic variation. The present study was conducted to induce variability through induced mutation, compare efficiency and effectiveness of gamma rays with electron beam on the basis of physiological changes in M1 generation; mutation frequency, spectrum of mutant phenotype and efficiency to produce novel mutations in M2 generation. Seeds of mungbean variety TM 96–2 were irradiated with doses of 200, 300, 400 and 500 Gy gamma rays and electron beam. On the basis of M 1 seedling growth, the effective mutagen dose (Growth Reduction Dose 50 i.e. GR 50 ) was 440 Gy of gamma rays and 470 Gy of electron beam for TM-96 –2. In M2 generation, electron beam treatments were found to induce greater frequency of chlorophyll mutations than gamma rays. The frequency of total mutants in electron beam (1.967) was found to be higher than gamma rays (1.343) along with mutation spectrum. The highest mutation spectrum was observed in 200 Gy dose of electron beam followed by 200 Gy gamma rays. Four novel mutants viz., four primary leaves in 400 Gy gamma rays, lanceolated leaves in 200, 300 and 500 Gy electron beam, yellow pod and yellow seed coat colour in 200 Gy treatment of electron beam were identified and isolated. Desirable mutants like early and synchronous maturity, large seed size and long root with drought tolerance were identified and isolated in different doses of both gamma rays and electron beam which were found true breeding in subsequent generations. Mutagenic efficiency of electron beam was higher in 200 and 400 Gy treatment as compared to same doses of gamma rays, while it was less than gamma rays in 300 and 500 Gy treatments. Mutagenic effectiveness was found to be highest in 200 Gy dose of electron beam which was more than twice that of the same dose of gamma rays. Highlights: Electron beam and gamma rays irradiation of Vigna radiata L. Wilczek. Electron beam induced greater frequency of chlorophyll mutations than gamma rays. Electron beam induced greater frequency and spectrum of morphological mutants. Higher efficiency and effectiveness of electron beam over gamma rays. Useful and novel mutants were induced through both gamma rays and electron beam.